The Diagnostic Value of the Thermostatic Amplification of Ribonucleic Acid in Bronchoalveolar Lavage Fluid in Smear-Negative Pulmonary Tuberculosis - Wu, Zhengxing; Shi, Jichan; Zhou, Yueying; Pan, Ning; Qiu, Chaochao; Wu, Lianpeng; Jiang, Xiangao (Frontiers in Public Health, 2022)
Objective: This study aimed to determine the value of the simultaneous amplification and testing for Mycobacterium tuberculosis in bronchoalveolar lavage fluid (BALF) in the diagnosis of smear-negative pulmonary tuberculosis (PTB). Methods: A total of 316 patients were selected, of which 197 had smear-negative PTB (observation group), and 119 did not have TB (control group). Bronchoscopy was performed in both groups, and BALF samples were collected for acid-fast bacilli smears, simultaneous amplification/testing for TB (SAT-TB), and BACTEC MGIT 960 cultures. The sensitivity, specificity, positive predictive and negative predictive values of SAT-TB in BALF for the diagnosis of negative TB were calculated. Results: The sensitivity of SAT-TB detection was 45.18%, which was significantly higher than smears and slightly lower than cultures. The specificity of SAT-TB was 99.16%, which differed slightly from the other two methods. The positive predictive value was 98.89%, which was not significantly different from the other two methods. The negative predictive value of SAT-TB was 58.91%, which was higher than smears and slightly lower than cultures. Conclusion: The very high specificity and negative prediction of SAT-TB in BALF mean that the method has great application value for the rapid diagnosis of smear-negative PTB.